2019
DOI: 10.1089/jayao.2018.0072
|View full text |Cite
|
Sign up to set email alerts
|

Oral Medication Adherence Among Adolescents and Young Adults with Cancer Before and Following Use of a Smartphone-Based Medication Reminder App

Abstract: This study evaluated oral medication adherence among adolescents and young adults (AYAs) with cancer during a trial of a smartphone-based medication reminder application (app). Methods: Twenty-three AYAs receiving at least one prescribed, scheduled oral medication related to their outpatient cancer treatment participated in this 12-week single-group interrupted time series longitudinal design study. Baseline oral medication adherence was monitored using electronic monitoring caps for 4 weeks. Participants then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…Applying this framework, we then reviewed evidence‐based adherence‐enhancing strategies (AESs) targeted toward key dimensions of adherence among AYAs (Table ). It should be noted that only two intervention studies targeting adherence exclusively among AYAs with cancer were identified . Given the limited literature examining strategies to enhance adherence among AYAs with cancer, this review also draws from evidence for AESs in AYAs with other chronic conditions with similar treatment demands to cancer.…”
Section: Conceptualizing Adherencementioning
confidence: 99%
See 3 more Smart Citations
“…Applying this framework, we then reviewed evidence‐based adherence‐enhancing strategies (AESs) targeted toward key dimensions of adherence among AYAs (Table ). It should be noted that only two intervention studies targeting adherence exclusively among AYAs with cancer were identified . Given the limited literature examining strategies to enhance adherence among AYAs with cancer, this review also draws from evidence for AESs in AYAs with other chronic conditions with similar treatment demands to cancer.…”
Section: Conceptualizing Adherencementioning
confidence: 99%
“…Finally, “forgetting” to take medications is a frequently cited barrier to adherence among the AYA population . Adolescents are neurodevelopmentally less future oriented than adults and have a different approach to managing and prioritizing competing demands .…”
Section: Dimensions Of Aya Adherencementioning
confidence: 99%
See 2 more Smart Citations
“…19 Oral medication nonadherence in the AYA population ranges between 27% and 60% and has been attributed to forgetfulness, a state of significant transition, and changing insurance status. 20,21 A pilot study done with 23 AYA patients using a smartphone application to improve adherence to oral medications found that >50% of patients took their medications with the reminders. 21 A recent study evaluated an application called ''Pain Squad''-a mobile health application that ''gamified'' pain assessment and management in the AYA population.…”
Section: Compliance Enhancement Technologymentioning
confidence: 99%